Creative Music Olah Ulah | Tabuh Kreasi Olah Ulahh” - Edy Upadana, I Ngurah (Pusat Penerbitan LPPMPP ISI Denpasar, 2024)
Tabuh Creation Olah Ulah is a musical composition inspired by the concept of tri guna, three essential human natures: animals, rajas, and tamas, which are different from each other. Satwam is calm, honest, kind, and wise. Rajas's nature is arrogant and haughty, while Tamas's is lazy and greedy. The three fundamental properties are interrelated and cannot be separated from each other. The concept is poured through the media, revealing Gamelan Semara Dhana, a new Gamelan barungan in the Karawitan of Bali. The method of creation used refers to the book